The Readiness of Indonesian Workers on Facing The Future World of Work - Rizki Gusfa Winda; Yulihasri; Hendra Lukito (Enrichment : Journal of Management, 2022)
This study aims to examine the effect of digital skills, industry 4.0 skill-sets, and instructor competencies on the work readiness of trainees at BLK Padang in facing the future world of work, by using a total sampling technique of 160 trainees, then the data analyzed by assisting of SPSS V 26, Mc. Excel, and PLS software 3.3. Results of the research show that digital skills, industry 4.0 skill-sets, and instructor competencies have a positive and significant effect on work readiness. Then, the moderation test showed that instructor competencies not only affect the work readiness of BLK Padang trainees but also strengthen the effects between digital skills and industry 4.0 skill-sets on work readiness of BLK Padang trainees.